An analysis of Romania's short-run sovereign rating determinants - Emilian Constantin Miricescu (Romanian Journal of Fiscal Policy (RJFP), 2012)
For most European Union countries the government expenditure exceeds government revenue which could lead in the long run to an increase in the government debt to GDP ratio. Considering the distortions generated by the financial and economic crisis, followed by the debt crisis, both local and international investors are more prudent when planning in lending money to sovereigns. The sovereign rating is probably one of the most important aspects which investors carefully analyze before they decide to purchase government bonds or Treasury bills. This paper focuses on Romania's short-run sovereign rating determinants according to the specific methodology of Romania's Export-Import Bank (EximBank). The results reveal that rating is Bb - payment difficulties and insignificant losses being possible.
Keywords: G15; C00; E44; F34; 330; Short-term sovereign rating; Scoring model; Fiscal policy; Public debt